2020
DOI: 10.3390/min10040310
|View full text |Cite
|
Sign up to set email alerts
|

Exploration Potential of Fine-Fraction Heavy Mineral Concentrates from Till Using Automated Mineralogy: A Case Study from the Izok Lake Cu–Zn–Pb–Ag VMS Deposit, Nunavut, Canada

Abstract: Exploration under thick glacial sediment cover is an important facet of modern mineral exploration in Canada and northern Europe. Till heavy mineral concentrate (HMC) indicator mineral methods are well established in exploration for diamonds, gold, and base metals in glaciated terrain. Traditional methods rely on visual examination of >250 µm HMC material, however this study applies modern automated mineralogical methods (mineral liberation analysis (MLA)) to investigate the finer (<250 µm) fraction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
2
20
0
1
Order By: Relevance
“…The MCHR ore required the lowest milling times to achieve the required target grinds. The milling times for the PCMZ and MCHR ore types at Nkomati are in broad agreement with those of the Merensky Reef and UG2 [53,58] and confirm the findings of Dzvinamurungu et al [53], that the milling times are primarily controlled by the chromite abundance.…”
Section: Milling Performances Of the Three Nkomati Mine Oressupporting
confidence: 86%
See 1 more Smart Citation
“…The MCHR ore required the lowest milling times to achieve the required target grinds. The milling times for the PCMZ and MCHR ore types at Nkomati are in broad agreement with those of the Merensky Reef and UG2 [53,58] and confirm the findings of Dzvinamurungu et al [53], that the milling times are primarily controlled by the chromite abundance.…”
Section: Milling Performances Of the Three Nkomati Mine Oressupporting
confidence: 86%
“…Graphite (milled to 100% passing 63 µm) in a 50:50 ratio with the sample was also added for particle separation and mixed with the epoxy resin. Further details can be found in Lougheed et al [58] and references therein. The modal mineralogy of the unprocessed ore (−2 mm crush) was also determined by preparing three 30 mm MLA mounts for each ore type.…”
Section: Methodsmentioning
confidence: 99%
“…SEM-AM facilitates studies that are not feasible with other methods. This is exemplified in the article by Lougheed et al [23] on the base metal exploration using heavy mineral concentrates (HMC). Traditional methods rely on visual examination of HMC fractions > 250 µm, but SEM-AM allows to investigate the finer fractions (<250 µm) as encountered in glacial till samples.…”
Section: The Special Issuementioning
confidence: 98%
“…Indicator mineral methods applied to sediment samples are important exploration tools for diamonds [1] and gold [2][3][4][5][6] in glaciated terrain. More recently, the potential of indicator minerals to aid in porphyry copper [7][8][9], magmatic Ni-Cu-platinum group elements (PGE; [6,10]), carbonate-hosted Pb-Zn [11], and volcanogenic massive sulfide (VMS) exploration [12,13] has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Automated mineralogy provides the potential for the identification and use of additional indicator minerals that traditional visual examination of the 250-2000 µm HMC fraction does not allow. An automated mineralogy method, MLA, was tested by Lougheed et al [13] using four archived Geological Survey of Canada (GSC) HMCs from till samples collected around the upper-amphibolite-facies Izok Lake volcanogenic massive sulfide deposit. Results indicated that MLA of the <250 µm HMC of till allowed the detection of both ore and alteration indicator minerals, with a notable increase in the areal extent of detectable sulfide dispersal down ice of Cu-Pb-Zn mineralization.…”
Section: Introductionmentioning
confidence: 99%